Study of homicidal death recorded at Forensic Medicine Department of Dinajpur Medical College (Journal of Dhaka National Medical College & Hospital, 2013)
Homicide is the most prevalent form of criminal offence in our country. It is also prevalent in other countries also. It is punishable under certain circumstances (Culpable Homicide) and not punishable under other circumstances (Excusable or justifiable Homicide). The punishment for homicide may be an imprisonment for life or even death sentence. A retrospective study was conducted on homicidal death in the Department of Forensic Medicine of Dinajpur Medical College. Above 300 cases were examined from January 2004 to December 2006 for 3 years. All the cases were referred from different police stations of Dinajpur district. Among them the highest number of cases were brought by Kotaali police Station about 12% and the lowest from Hakimpur Police Station about 2.5%. Out of 300 cases 70% victims were male Muslims. The highest frequency of offence was found in lower socioeconomic groups. The age group of them was from 32 to 45 years.J.Dhaka National Med. Coll. Hos. 2013; 19 (02): 40-41